Spatial Decay of Groundwater Quality Along a Dumpsite-To-Receptor Distance Gradient: Water Quality Index Assessment and Human Health Risk Estimation for Peri-Urban Benin City, Nigeria (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Groundwater contamination by open dumpsites is one of the most widespread but least quantified public health concerns in Sub-Saharan Africa's peri-urban areas. Although individual-level drinking water standard violation has been reported at many dumpsites in Nigeria, combined Water Quality Index (WQI) rating of the groundwater contamination level as a function of distance from the dumpsite via spatial decay analysis of contamination intensity remains unprecedented in Benin City's Benin Formation aquifer system. This study utilizes the WQI method and Human Health Risk Assessment (HHRA) protocol as per the USEPA guidelines to analyze the groundwater quality data from eight borehole wells located at varying distances ranging from 100 meters up to about 800 meters from the Upper Ekehuan (Asoro) open dumpsite in Ovia North-East LGA, Edo State, Nigeria. WQI scores ranged from 198.4 (100 m borehole, 'Very Poor') to 89.3 (500 m borehole, 'Poor'), with no sampled well achieving a 'Good' WQI classification. Spatial regression analysis reveals a statistically significant exponential decay in composite contamination intensity with increasing distance (R² = 0.84). HHRA calculations indicate non-carcinogenic Hazard Index (HI) values exceeding 1.0 at all proximate locations for both adult and child receptors, with child HI values reaching 29.4. Carcinogenic risk from Chromium(VI) and Cadmium exceeds the USEPA acceptable risk level of 1×10⁻⁴ at all wells within 300 meters. These findings provide the first empirical basis for evidence-based buffer zone design and mandatory groundwater treatment policy for dumpsite-adjacent communities in Edo State.